Budaya Patriarki dan Implikasinya terhadap Perlindungan Hukum bagi Perempuan di Indonesia - Rolita Kosta Bunga; Agra Sifa Illahi; Daniel Sitinjak (GLOBAL SCIENTS PUBLISHER, 2025)
Patriarchal culture is a social system that places men at the center of power and domination in society, while women are in a lower position and often experience injustice. In the Indonesian context, patriarchal culture is still very strong and influential in various aspects of life, including in the field of law. Although the government has issued various regulations aimed at protecting women, such as Law Number 23 of 2004 concerning the Elimination of Domestic Violence and Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, in reality, the implementation of these laws is still not fully effective. This is due to the persistence of gender bias among the public and law enforcement officials. As a result, many women victims of violence find it difficult to obtain justice and adequate legal protection. This journal aims to analyze how patriarchal culture affects legal protection for women in Indonesia and to offer solutions for creating a legal system that is more just, equitable, and free from gender discrimination.